FOXP3+ T Regulatory Cell Modifications in Inflammatory Bowel Disease Patients Treated with Anti-TNFα Agents. (24th August 2013) - Guidi, Luisa; Felice, Carla; Procoli, Annabella; Bonanno, Giuseppina; Martinelli, Enrica; Marzo, Manuela; Mocci, Giammarco; Pugliese, Daniela; Andrisani, Gianluca; Danese, Silvio; De Vitis, Italo; Papa, Alfredo; et al.
Abstract : Treg modulation has been hypothesized as one of the mechanisms by which antitumor necrosis factor α (TNF α ) agents exert their action in rheumatoid arthritis (RA) and inflammatory bowel disease (IBD). However, data in IBD are still conflicting. We evaluated CD4 + CD25 + FOXP3 + (Tregs) by flow cytometry in peripheral blood from 32 adult IBD patient before (T0) and after the induction of anti-TNF α therapy (T1). Eight healthy controls (HCs) were included. We also evaluated the number of FOXP3 + cells in the lamina propria (LP) in biopsies taken in a subset of patients and controls. Treg frequencies were significantly increased in peripheral blood from our patients after anti-TNF α therapy compared to T0. T1 but not T0 levels were higher than HC. The increase was detectable only in clinical responders to the treatment. A negative correlation was found among delta Treg levels and the age of patients or disease duration and with the activity score of Crohn's disease (CD). No significant differences were found in LP FOXP3 + cells. Our data suggest the possibility that in IBD patients the treatment with anti-TNF α may affect Treg percentages and that Treg modifications may correlate with clinical response, but differently in early versus late disease.